2017
DOI: 10.3171/2016.7.peds1655
|View full text |Cite
|
Sign up to set email alerts
|

Failure of ETV in patients with the highest ETV success scores

Abstract: OBJECTIVEEndoscopic third ventriculostomy (ETV) is a surgical alternative to placing a CSF shunt in certain patients with hydrocephalus. The ETV Success Score (ETVSS) is a reliable, simple method to estimate the success of the procedure by 6 months of postoperative follow-up. The highest score is 90, estimating a 90% chance of the ETV effectively treating hydrocephalus without requiring a shunt. Treatment with ETV fails in certain patients, despite their being the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Although VPS may be considered the historical gold standard for CSF diversion, the high failure rates and potential for infection make this an undesirable option both for patients and physicians. Therefore, the current literature supports the notion that use of ETV has an overall higher success rate, as predicted by ETVSS, than VPS when managing obstructive hydrocephalus from tectal gliomas [8,15]. Regardless of the failure rate in either procedure, CSF diversion still remains the most commonly performed procedure in pediatric patients with tectal gliomas and is an effective management strategy for treatment and symptomatic relief of associated hydrocephalus in these patients.…”
Section: Management Of Hydrocephalussupporting
confidence: 54%
See 1 more Smart Citation
“…Although VPS may be considered the historical gold standard for CSF diversion, the high failure rates and potential for infection make this an undesirable option both for patients and physicians. Therefore, the current literature supports the notion that use of ETV has an overall higher success rate, as predicted by ETVSS, than VPS when managing obstructive hydrocephalus from tectal gliomas [8,15]. Regardless of the failure rate in either procedure, CSF diversion still remains the most commonly performed procedure in pediatric patients with tectal gliomas and is an effective management strategy for treatment and symptomatic relief of associated hydrocephalus in these patients.…”
Section: Management Of Hydrocephalussupporting
confidence: 54%
“…While CSF diversion is the most utilized procedure, it is still prone to failure. Despite an ETV success score generally predicting up to 90% ETV success rate, in cases of failure, patients may require a second ETV procedure or may be switched to a shunt [8,15,24]. The reports of failure in these procedures have been variable among the published literature.…”
Section: Management Of Hydrocephalusmentioning
confidence: 99%
“…According to previous reports, age, etiology, and experience of the surgeon are important factors that determine success and complication rates of ETV [ 9 ]. Higher success rates, reaching 90%, in some studies have been reported in infants with aqueductal stenosis [ 10 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gianaris et al showed 3 factors that may contribute to failure in those with a high ETVSS: preoperative lethargy, preoperative radiological finding of transependymal flow, and postoperative mTVW. 6 We evaluated those 3 factors, but none showed statistical significance (data not shown). That may be due to the small number of subjects, so further larger studies might be needed to confirm those factors.…”
Section: Radiological Parameters Before and After Etvmentioning
confidence: 99%